Using a computer game to assess the critical thinking skills of preschoolers: A pilot study - Ow, S.H. (2017)
Many employers find today’s graduates are lacking in critical thinking (CT), creativity and problem solving skills. Research findings show that these skills, especially critical thinking skills, can be taught during early childhood education. To develop and foster CT skills among children, an assessment need to be made to identify which of the CT components that they are weak in. Currently, there are many CT skills evaluation instruments for job employment and school enrollment. However, there are no assessment instruments for preschool children aged 4-6 years. This paper presents a pilot study on the assessment of CT skills among 20 preschool children aged 5-6 years using a computer game. The CT skills components evaluated include knowledge, comprehension, application, analysis, evaluation, and inference. The findings of the pilot study show that computer game can be a useful and practical tool for assessing and fostering the CT skills of preschoolers. Based on the game scores, the 20 children were found to perform well in Classification, Sequence of Events and Word Match sub-games, but poorly in Facts or Opinion, Divide and Conquer and Transformation sub-games. These outcomes imply that they comprehend what they learned in kindergartens, but they are weak in analysing, evaluating, applying, and making inference during problem-solving.